Amendment to the act on civilian victims of war and the legal situation of children of war rape in Bosnia and Herzegovina - Czeszejko-Sochacka, Katarzyna (Polityka i Społeczeństwo, 2023)
War rape is a phenomenon that occurs in almost every armed conflict. The circle of victims includes not only the persons directly affected by this crime, but also their next of kin. Unwanted pregnancies as a result of wartime rape result in children who, from the moment they are born, are treated as inferior persons. Apart from marginal cases, the internal laws of individual states do not grant them any protection or compensation. For some time now, however, a change in this direction has been evident on the international stage. Bosnia and Herzegovina is the first European country which has responded to these calls and has taken steps to change the status of children from war rape.